Push!: exploring the myth of childbirth in Malay films - Jamaluddin Aziz,; Jamila Mohd,; Norhayati Haji Hamzah,; Abdulhamid Badru, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Childbirth is a universal and natural global experience, however, its representation in films specifically, and popular culture in general, is framed within stereotypical images that are brimming over with inaccuracy and myth. In the West, gynae-narratives in films are often studied by using feminist psychoanalysis, particularly on the gynae-horror narrative. This study, explores the varied representations of childbirth in some selected Malay films - such as the labouring body - to identify and make sense of why the experience of childbirth in films becomes rather problematic, asking the question of what myth is being perpetuated by such representations. Using a close textual analysis of some Malay films that are purposively selected, the study employs Roland Barthes’ Myth and its link to ideology as a critical framework, paying attention to Malay cultural signs to create meanings and expose the ideological motives of such representation. This study is crucial for it is able to illuminate the myth-making process of childbirth in Malay films and the effects this myth might have on the society’s view of the experience of childbirth, and perhaps putting into microscope our cultural perceptions of marriage, motherhood, womanhood, the female body and the family.